Repeat infection with SARS COV-2, a worrisome situation: report of two cases from India - Kumar, Deepak; Gupta, Garima (International Journal Of Community Medicine And Public Health, 2021)
Number of COVID cases and mortalities are still growing globally. There is no single treatment method found effective in reducing the disease severity. Several vaccines have been developed recently and most of them are under clinical trial only. Availability of an effective vaccine and its use at the community level is the only hope left with us. However, the emergence of re-infective cases from various part of the world has put a big question on the ongoing vaccination research and its use. Most of these re-infection cases reported were not studied for viral genome, different mutated virus causing repeat infection have been isolated in few reports only. In these situations, either a newer vaccine has to be developed every time for a new mutated virus or the multiple doses of the vaccine have to be administered if same strain of the virus is causing the re-infection. We report two cases from India who acquired repeat SARS COV 2 infection, adding up the much-required information in the current scenario.